Representation of decimal fractions as simple fractions in elementary grades (Texas Journal of Multidisciplinary Studies, 2022)
In this article, we will analyze how ordinary fractions are converted to decimal fractions, and also consider the reverse process - the conversion of decimal fractions to ordinary fractions.